1997
DOI: 10.1128/iai.65.12.4996-5002.1997
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic intragastric vaccination against Helicobacter pylori in mice eradicates an otherwise chronic infection and confers protection against reinfection

Abstract: Chronic infection of the gastroduodenal mucosae by the gram-negative spiral bacterium Helicobacter pylori is responsible for chronic active gastritis, peptic ulcers, and gastric cancers such as adenocarcinoma and low-grade gastric B-cell lymphoma. The success of eradication by antibiotic therapy is being rapidly hampered by the increasing occurrence of antibiotic-resistant strains. An attractive alternative approach to combat this infection is represented by the therapeutic use of vaccines. In the present work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(57 citation statements)
references
References 44 publications
(69 reference statements)
7
49
1
Order By: Relevance
“…The therapeutic vaccination of H. pylori-infected mice using H. pylori-whole cell sonicate together with the mucosal adjuvant CT induced a high level of eradication. This is in full agreement with previous studies (2,3,6,9,23) (Table 1).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The therapeutic vaccination of H. pylori-infected mice using H. pylori-whole cell sonicate together with the mucosal adjuvant CT induced a high level of eradication. This is in full agreement with previous studies (2,3,6,9,23) (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we demonstrated that chronic gastric infection by H. pylori in mice can be successfully cured with the oral administration of H. pylori-whole cell sonicate plus CT as an adjuvant. Several investigators have recently suggested that therapeutic oral vaccination against H. pylori infection is effective for bacterial eradication (2,3,6,9,11,23). Doidge et al firstly indicated the feasibility of therapeutic vaccination against H. felis infection in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial mechanism of protection or whether other aspects of the immune system, such as IgG from mucosa in-ghosts have been produced from a variety of bacteria including E. coli and H. pylori. Oral, aerogenic or filtrated B cells or cell mediated responses, are more important remains to be established (87). Prophylactic parenteral administration of (recombinant) ghosts (Rghosts) in experimental animals induced specific and therapeutic immunity against H. pylori obtained with various formulations, in rodent, cat and monkey humoral and cellular immune responses against bacterial and target components including protective mu-models have been attributed to an expression of MHC II-restricted T cell effectors rather than sIgA (88).…”
Section: Adherin Proteinsmentioning
confidence: 99%
“…In mice, orogastric vaccination with mucosal adjuvants and H. pylori whole cell sonicate or individual antigens, such as urease or vacuolating cytotoxin (VacA), prevented H. pylori infection [4]. Orogastric vaccination with VacA also eradicated chronic H. pylori infection in mice [5]. In human volunteers, experimental vaccination with urease resulted in a decrease of the H. pylori infective load of the stomach only [6].…”
Section: Introductionmentioning
confidence: 99%